On the Typical Spectral Shape of an Economic Variable - Daniel Levy; Hashem Dezhbakhsh (Applied Economics Letters, 2003)
In a classic article, Granger (Econometrica 34, 1966) asserted that most economic time series measured in level have spectra that exhibit a smooth declining shape with considerable power at very low frequencies. There has been no systematic attempt to examine Granger's assertion with international data. Output level spectra are estimated for 58 countries, divided into developed, high-income developing, and low-income developing groups. The shapes of the estimated spectra are found to be strikingly similar to Granger's typical shape, particularly for the developed countries.
Keywords: E32; O40; O57; 330; Spectral Analysis; Spectral Shape; Output Level; OECD; and Developing Countries